2015
DOI: 10.1002/adem.201500073
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Strain Rate on Tensile Ductility and Fracture Behavior of Bulk Nanotwinned Copper

Abstract: A bulk columnar-grained copper with preferentially oriented nanoscale growth twins is prepared by means of direct-current electrodeposition. Tensile tests at different strain rates reveal a significant influence of strain rate on the tensile ductility and fracture behavior. The ductility, especially the postnecking elongation, reduces dramatically at low strain rates, which is associated with evident intergranular fracture. The results suggest that the grain size as well as the grain boundary microstructural e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…As the mechanical properties of materials are directly related to their deformation mechanisms [6][7][8][9][10][11][12][13][14], revealing the atomic-scale deformation mechanisms of materials is important for understanding their mechanical performance and realizing their desired mechanical properties [11,12,[15][16][17][18]. In recent decades, a large number of studies have been conducted on the deformation mechanisms of twin-structured metals [16][17][18][19][20][21][22][23][24][25][26][27][28]. Many molecular dynamics (MD) simulations and experimental investigations have suggested that the ultrahigh strength of twin-structured metals results from partial dislocations intersecting with coherent twin boundaries (CTBs) [10,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…As the mechanical properties of materials are directly related to their deformation mechanisms [6][7][8][9][10][11][12][13][14], revealing the atomic-scale deformation mechanisms of materials is important for understanding their mechanical performance and realizing their desired mechanical properties [11,12,[15][16][17][18]. In recent decades, a large number of studies have been conducted on the deformation mechanisms of twin-structured metals [16][17][18][19][20][21][22][23][24][25][26][27][28]. Many molecular dynamics (MD) simulations and experimental investigations have suggested that the ultrahigh strength of twin-structured metals results from partial dislocations intersecting with coherent twin boundaries (CTBs) [10,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon is associated with plastic relaxation occurring in the vicinity of GBs once the local dislocation density or stress is larger than some critical value. Among the possible relaxation processes are dislocation reconfiguration leading to the formation of dislocation cells or sub-grains [11,14], localized destruction of growth nanotwins [14,34], and even intergranular cracking that appears to be enhanced at low strain rates [13].…”
Section: Resultsmentioning
confidence: 99%
“…There have been plenty of investigations dealing with the mechanisms how microstructural parameters, such as twin thickness, twin boundary (TB) orientation, and grain diameter (or twin length), influence the mechanical response, especially for their unique strain hardening behavior [9][10][11][12][13]. For example, in columnar-grained NT Cu with TBs in most grains highly aligned with the tensile direction, it has been demonstrated that plastic deformation tends to concentrate along grain boundaries (GBs), resulting in a strong dependence of tensile ductility on grain size [14].…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical performance of metals and alloys is always sensitive to strain rates, especially for NC metals [98][99][100][101][102][103]. The SRS can be defined as: = ⁄ , where σ is the flow stress and ε is the strain rate.…”
Section: Strain Rate Effect and Activation Volumementioning
confidence: 99%
“…ε is the strain rate. SRS generally reflects the ability of materials to resist localized deformation when deformation is unstable at higher strain rate [71,[98][99][100][101][102][103]. In general, the high SRS means higher elevation in flow stress with increasing strain rate.…”
Section: Strain Rate Effect and Activation Volumementioning
confidence: 99%